Respiratory Muscle Weakness in Thyrotoxic Periodic Palsy: A Lesson to Remember. Issue 3 (July 2021) - Sethi, Prativa Priyadarshani; Parchani, Ashwin; Pathania, Monika
Thyrotoxic periodic palsy (TPP) is a sporadic form of hypokalemic periodic palsy that may occur in association with hyperthyroidism mostly with Graves' disease. Acute thyrotoxic periodic palsy is a disorder most commonly seen in Asian men and characterized by abrupt onset of hypokalemia and paralysis. The disorder primarily affects the lower extremities and can involve all four limbs and presents as acute flaccid paralysis. The diagnosis of thyrotoxic periodic palsy is not difficult, but the disease's low incidence and many differentials for acute flaccid paralysis delay and complicate the diagnosis. TPP is not related to the etiology, severity, and duration of thyrotoxicosis. The treatment is similar to hypokalemic periodic palsy with potassium supplementation and initiation of antithyroid drugs and beta-blocker therapy. Here a similar case of quadriparesis is reported, which got precipitated after abrupt cessation of carbimazole in a young male. This initially was thought to be a case of hypokalemic periodic palsy and was later diagnosed to be TPP and recovered after initiating antithyroid drugs and potassium supplementation.